2005
DOI: 10.1002/anie.200462424
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Catalysis by General Acid and Base Bifunctionalized Mesoporous Silica Nanospheres

Abstract: A team effort: Mesoporous silica nanosphere (MSN) materials bifunctionalized with a general acid group and a base group in various relative concentrations are described and shown to function as cooperative catalytic systems. The turnover numbers observed indicate that the acid groups can activate substrates in cooperation with the base groups to catalyze reactions that involve carbonyl activation (see picture).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
191
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 349 publications
(195 citation statements)
references
References 18 publications
(14 reference statements)
3
191
0
1
Order By: Relevance
“…Indeed, the weakly acidic silanol groups on the surface of silica have been previously recognized as capable of assisting various reactions. [23,[45][46][47][48][49] To test the participation of silanol groups in the catalytic process, we treated MAP-MSN-3.5 with hexamethyldisilazane (HMDS). 29 Si NMR showed that this reduced the number of silanols by 39% (from 3.8 to 2.3 mmol/g, Figure 4).…”
Section: Cooperative Effects Of the Supportmentioning
confidence: 99%
“…Indeed, the weakly acidic silanol groups on the surface of silica have been previously recognized as capable of assisting various reactions. [23,[45][46][47][48][49] To test the participation of silanol groups in the catalytic process, we treated MAP-MSN-3.5 with hexamethyldisilazane (HMDS). 29 Si NMR showed that this reduced the number of silanols by 39% (from 3.8 to 2.3 mmol/g, Figure 4).…”
Section: Cooperative Effects Of the Supportmentioning
confidence: 99%
“…A cooperative catalytic mechanism that 90 emulates enzymatic chemistry was proposed to explain this unique behavior (Figure 3). 114 A later study found a dependency of the catalytic activity of the bi-functional materials on the density of the immobilized groups. Besides creating cooperative interactions, the introduction of two functional groups in MSN can be exploited to attain another desirable characteristic in a catalyst: selectivity.…”
mentioning
confidence: 96%
“…These heterogeneous bifunctional catalysts can be categorized into three types: (1) catalysts possessing both an immobilized Brønsted acid site and a basic site derived from organic groups, (2) immobilized basic organic groups and Brønsted acid sites derived from the support surface, and (3) immobilized metal complexes or metal nanoparticles and basic organic groups. For a type (1) catalyst, in 2005, Lin and co-workers demonstrated a urea _ amine bifunctionalized silica surface for carbon _ carbon bond-forming reactions, such as an aldol reaction 6) . The first report on the immobilization of two incompatible groups, such as an organic acid (carboxylic or sulfonic acid), and a base, on the same catalyst particle surface was reported by Davis and co-workers in 2006 7) .…”
Section: Introductionmentioning
confidence: 99%